Analysis of DNA structure and sequence requirements for Pseudomonas aeruginosa MutL endonuclease activity - Correa, Elisa María Eugenia (2013)
The hallmark of the mismatch repair system in bacterial and eukaryotic organisms devoid of MutH is the presence of a MutL homologue with endonuclease activity. The aim of this study was to analyse whether different DNA structures affect Pseudomonas aeruginosa MutL (PaMutL) endonuclease activity and to determine if a specific nucleotide sequence is required for this activity. Our results showed that PaMutL was able to nick covalently closed circular plasmids but not linear DNA at high ionic strengths, while the activity on linear DNA was only found below 60 mM salt. In addition, single strand DNA, ss/ds DNA boundaries and negatively supercoiling degree were not required for PaMutL nicking activity. Finally, the analysis of the incision sites revealed that PaMutL, as well as Bacillus thuringiensis MutL homologue, did not show DNA sequence specificity.